Study the technical validity and feasibility of serum HER-2/Neu and its correlation with tissue HER-2 status in female breast cancer patients only - Sufia Ahmad Khan; Renu Sahay; Basundhara Sinha (Asian Journal of Medical Sciences, 2023)
Background: Breast cancer is one of the leading causes of death in women worldwide. The future burden of breast cancer is predicted to increase over 3 million new cases and 1 million deaths in 2040. In India, it is being increasingly diagnosed at a younger age as compared to the west. Human epidermal growth factor receptor 2 (HER-2) transmembrane protein, with a molecular weight 185 kDa, plays a key role in cell growth and its overexpression favors cell proliferation by inhibiting apoptosis. HER-2 extracellular domain, released into blood before appearing into tissue, can be easily detected by enzyme-linked immunosorbent assay (ELISA) using serum. HER-2 has many roles in assisting diagnosis, targeted therapy, and evaluating prognosis. Aims and Objectives: The study aimed to monitor the serum HER-2 level and its correlation with tissue HER-2 status in breast cancer patients. Materials and Methods: We performed a prospective study on technical validity and feasibility of serum HER-2 level by ELISA in breast cancer patients and its correlation with tissue HER-2 status by immunohistochemistry (IHC) method. Results: We found the serum ELISA level was raised and within the reference range in all breast cancer patients. A higher level of serum HER-2 level was seen in high tumor stage, high Nottingham grade, and with axillary lymph node metastasis. Serum HER-2 level was significantly higher in IHC score 3+ as compared to score 2+and 1+. Conclusion: This study concluded that serum HER-2 ELISA is a valid and feasible test. Association of serum HER-2 level with tumor stage; Nottingham grade; and axillary nodal metastasis was significant. The correlation between serum HER-2 and tissue HER-2 was found significant. Thus, serum HER-2 may be used as an early diagnostic and prognostic biomarker to guide in clinical practice.